Evaluasi Geometri dan Perlengkapan Jalan Lingkar Leuwiliang Bogor - Dzaky Syifaurrahman; Muhammad Fauzan; Tri Sudibyo (Jurnal Teknik Sipil dan Lingkungan, 2019)
Leuwiliang Ring Road had curve, slop and road equipment like signs, markers and street lighting that uncomfortable for drivers. The purpose of this research was to evaluate road geometric based on RSNI T-14-2004 and guidelines no. 038/TBM/1997 and road equipment based on guidelines no. 01/P/BNKT/1991 and SNI 7391: 2008 on Jalan Lingkar Leuwiliang. The results showed that design of geometry and equipment of this road did not conform to Standard. The speed limit used was 50 km/h. The free side area on the 4th curve was of 3 m less than Standard (3.04 m). Slopes of the road were more than 9% on segment 2 (14.21%), 4 (10.94%), 13 (9.01%), 14 (9.19%), 26 (9.20%), 27 (9.20%), 28 (9.49%), 29 (12.15%) and 30 (19.36%). There were no markers on this road then longitudinal line mark was designed on the road side. Dotted line marks were designed at Sta 0+000 to Sta 0+200 and longitudinal line mark were designed at Sta 0+200 to Sta 0+974.5 on the road divider. There were no street lighting on the 7th pole to the 22nd pole so the street lighting were designed on that poles using the lamp type SON 100W patch to the pole with height of 6 m from the road surface.Keywords : free side area, lamp, road, road markings, slope.